2020
DOI: 10.1371/journal.pntd.0008199
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate time-series analysis of biomarkers from a dengue cohort offers new approaches for diagnosis and prognosis

Abstract: Dengue is a major public health problem worldwide with distinct clinical manifestations: an acute presentation (dengue fever, DF) similar to other febrile illnesses (OFI) and a more severe, life-threatening form (severe dengue, SD). Due to nonspecific clinical presentation during the early phase of dengue infection, differentiating DF from OFI has remained a challenge, and current methods to determine severity of dengue remain poor early predictors. We present a prospective clinical cohort study conducted in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…The role of blood biomarkers in predicting severe outcomes has been investigated in many studies, but mostly at later time-points or at hospital admission and many of these biomarkers either peak too late in the disease course or have too short a half-life to be clinically useful ( Ab-Rahman et al, 2016 ; John et al, 2015 ; Oliveira et al, 2017 ; Puerta-Guardo et al, 2019 ; Rathore et al, 2020 ; Robinson and Einav, 2020 ; S S et al, 2017 ; Soo et al, 2017 ; Vasey et al, 2020 ; Yacoub et al, 2017 ; Yacoub et al, 2016b ; Yong et al, 2017 ). Acknowledging these characteristics, we selected 10 candidate biomarkers from the vascular, immunological, and inflammatory pathways with good evidence supporting their involvement in the pathogenesis of dengue infection – focusing on those likely to be increased early in the disease course.…”
Section: Introductionmentioning
confidence: 99%
“…The role of blood biomarkers in predicting severe outcomes has been investigated in many studies, but mostly at later time-points or at hospital admission and many of these biomarkers either peak too late in the disease course or have too short a half-life to be clinically useful ( Ab-Rahman et al, 2016 ; John et al, 2015 ; Oliveira et al, 2017 ; Puerta-Guardo et al, 2019 ; Rathore et al, 2020 ; Robinson and Einav, 2020 ; S S et al, 2017 ; Soo et al, 2017 ; Vasey et al, 2020 ; Yacoub et al, 2017 ; Yacoub et al, 2016b ; Yong et al, 2017 ). Acknowledging these characteristics, we selected 10 candidate biomarkers from the vascular, immunological, and inflammatory pathways with good evidence supporting their involvement in the pathogenesis of dengue infection – focusing on those likely to be increased early in the disease course.…”
Section: Introductionmentioning
confidence: 99%
“…Time-series analysis was then integrated with TI analysis to uncover the regulatory factors implied in dynamic biological processes in a quantitative way. Time-series analysis has been successfully applied in studies focusing on human disease and drug development [18] , [19] . Therefore, time-series analysis clearly takes full advantage of the time-series information involved in dynamic processes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, time-series analysis [17] that can take into account the information generated at several time points at the same time, determine expression patterns (such as cyclical pattern), and identify regulatory factors in a dynamic biological process in a quantitative and knowledge-free way, will be a perfect choice for time series scRNA-seq data obtained from multiple snapshots. At present, time-series analysis is being successfully applied in studies focusing on human disease and drug development [18] , [19] . Although not applied to scRNA-seq data, the advantage of time-series analysis in identifying DEGs in dynamic biological processes based on high-throughput RNA-seq data has also been revealed [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in fibrinogen levels can be explained by higher consumption due to the procoagulant state but also due to extravasation and decreased hepatic fibrinogen synthesis. However, it has been suggested that fibrinolysis in secondary dengue virus infections is not as prominent as in primary infections [ 57 ]. In our study, significantly low levels of fibrinogen, although still within the normal range, were found in DwWS/SD patients compared to DwoWS patients.…”
Section: Discussionmentioning
confidence: 99%